2022
DOI: 10.1002/adma.202108446
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Soluble Organic Photocatalyst Discovered for Highly Efficient Additive‐Free Visible‐Light‐Driven Grafting of Polymers from Proteins at Ambient and Aqueous Environments

Abstract: Since the pioneering discovery of a protein bound to poly(ethylene glycol), the utility of protein–polymer conjugates (PPCs) is rapidly expanding to currently emerging applications. Photoinduced energy/electron‐transfer reversible addition–fragmentation chain‐transfer (PET‐RAFT) polymerization is a very promising method to prepare structurally well‐defined PPCs, as it eliminates high‐cost and time‐consuming deoxygenation processes due to its oxygen tolerance. However, the oxygen‐tolerance behavior of PET‐RAFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…In contrast to the normal oxygen tolerance behavior, Boyer et al reported an oxygen-mediated reductive quenching process during PET-RAFT polymerization, where the polymerization rate was considerably enhanced in the presence of both oxygen and sacrificial reducing agents (e.g., tertiary amines) under red-NIR illumination . Kwon et al reported the “oxygen-acceleration” phenomenon during the PET-RAFT polymerization of different acrylic and acrylamide monomers in the absence of sacrificial reducing agents and the presence of the newly designed PC . Both studies indicated that oxygen acts as a catalyst to facilitate the electron transfer between the PC in the excited state and the RAFT agent (Figure f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the normal oxygen tolerance behavior, Boyer et al reported an oxygen-mediated reductive quenching process during PET-RAFT polymerization, where the polymerization rate was considerably enhanced in the presence of both oxygen and sacrificial reducing agents (e.g., tertiary amines) under red-NIR illumination . Kwon et al reported the “oxygen-acceleration” phenomenon during the PET-RAFT polymerization of different acrylic and acrylamide monomers in the absence of sacrificial reducing agents and the presence of the newly designed PC . Both studies indicated that oxygen acts as a catalyst to facilitate the electron transfer between the PC in the excited state and the RAFT agent (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…This “oxygen-acceleration” behavior was also observed for other types of methacrylic monomers; however, oligo­(ethylene glycol) methyl ether methacrylate (OEGMA) exhibited it most notably, as depicted in Figure e. It is worth noting that “oxygen-acceleration” behavior was recently reported by Boyer et al and Kwon et al , Without degassing and with excellent conversion and polymerization control (α = 97%, M n = 28 600, Đ = 1.08), block copolymer synthesis (PMMA- b -PBzMA) was accomplished, confirming the high vitality of the reaction under those conditions (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…40 Furthermore, the removal of the requirement for harsh buffer solvents and the use of non-toxic, environmentally friendly water as solvent, coupled with the recyclability of the heterogeneous phase, promises to expand its use in biomedical applications such as protein-polymer conjugates. 41,42 Mechanistic validation of the OH • -RAFT protocol catalyzed by heterogeneous COF-based bionic enzymes…”
Section: Papermentioning
confidence: 99%
“…Subsequently, the PET-RAFT protocol of the oxygen-mediated reductive quenching pathway (O-RQP) was defined and its thermodynamic constraints were clarified by density functional theory (DFT) calculations, providing an attractive avenue for the development of oxygen-catalyzed processes . Kwon et al exploited a water-soluble and biocompatible organic small-molecule catalyst to propose a PET-RAFT protocol with molecular oxygen as the electron shuttle, without additional electron sacrificial amine addition …”
Section: Introductionmentioning
confidence: 99%